Filamin A is a phosphorylation target of membrane but not cytosolic adenylyl cyclase activity - Sayner, Sarah L. (American Physiological Society, 2011)
Transmembrane adenylyl cyclase (AC) generates a cAMP pool within the subplasma membrane compartment that strengthens the endothelial cell barrier. This cAMP signal is steered toward effectors that promote junctional integrity and is inactivated before it accesses microtubules, where the cAMP signal causes phosphorylation of tau, leading to microtubule disassembly and barrier disruption. During infection, Pseudomonas aeruginosa uses a type III secretion system to inject a soluble AC, ExoY, into the cytosol of pulmonary microvascular endothelial cells. ExoY generates a cAMP signal that disrupts the endothelial cell barrier. We tested the hypothesis that this ExoY-dependent cAMP signal causes phosphorylation of tau, without inducing phosphorylation of membrane effectors that strengthen endothelial barrier function. To approach this hypothesis, we first discerned the membrane compartment in which endogenous transmembrane AC6 resides. AC6 was resolved in caveolin-rich lipid raft fractions with calcium channel proteins and the cell adhesion molecules N-cadherin, E-cadherin, and activated leukocyte adhesion molecule. VE-cadherin was excluded from the caveolin-rich fractions and was detected in the bulk plasma membrane fractions. The actin binding protein, filamin A, was detected in all membrane fractions. Isoproterenol activation of ACs promoted filamin phosphorylation, whereas thrombin inhibition of AC6 reduced filamin phosphorylation within the membrane fraction. In contrast, ExoY produced a cAMP signal that did not cause filamin phosphorylation yet induced tau phosphorylation. Hence, our data indicate that cAMP signals are strictly compartmentalized; whereas cAMP emanating from transmembrane ACs activates barrier-enhancing targets, such as filamin, cAMP emanating from soluble ACs activates barrier-disrupting targets, such as tau.